Single-stage synthesis of 3-hydroxy- and 3-alkoxy-5-arylimidazolidine-2,4-diones by reaction of arylglyoxal hydrates with N-hydroxy- and N-alkoxyureas - Shtamburg, Vasiliy G.; Штамбург, Василь Григорович; Shtamburg, Viktor V.; Штамбург, Віктор Васильович; Anishchenko, Andrey A.; Аніщенко, Андрій Олександрович; Zubatyuk, Roman I.; Зубатюк, Роман Іванович; Mazepa, Aleksander V.; Мазепа, Олександр Васильович; Klotz, Eugene A.; Клоц, Євген А.; et al. (Springer Nature, 2015)
Arylglyoxal hydrates interact with N-alkoxyureas and N-hydroxyurea in acetic acid with selective formation of 3-alkoxy-5-arylimidazolidine-2,4-diones and 5-aryl-3-hydroxyimidazolidine-2,4-diones, respectively. The structures of 3-methoxy-5-phenylimidazolidine-2,4-dione, 3-ethoxy-5-phenylimidazolidine-2,4-dione, and 3-butoxy-5-(4-chlorophenyl)imidazolidine-2,4-dione were studied by X-ray structural analysis. Гідрати арилгліоксалю взаємодіють з N -алкоксісечовинами та N -гідроксисечовиною в оцтовій кислоті з селективним утворенням 3-алкокси-5-арилімідазолідин-2,4-діонів та 5-арил-3-гідроксіімідазолідин-2,4-діонів відповідно. Структури 3-метокси-5-фенілімідазолідин-2,4-діону, 3-етокси-5-фенілімідазолідин-2,4-діону та 3-бутокси-5-(4-хлорфеніл)імідазолідин-2,4-діону досліджено методом рентгеноструктурного аналізу.
Одностадійний синтез 3-гідрокси- та 3-алкокси-5-арилімідазолідин-2,4-діонів реакцією арилгліоксальгідратів з N -гідрокси- та N –алкоксісечовинами
Keywords: 3-alkoxy-5-arylimidazolidine-2,4-diones; 3-алкокси-5-арилімідазолідин-2,4-діони; N-alkoxyureas; N -алкоксісечовини; arylglyoxals; арилгліоксалі; 5-aryl-3-hydroxyimidazolidine-2,4-diones; 5-арил-3-гідроксіімідазолідин-2,4-діони; N-hydroxyurea; N -гідроксисечовина; cyclization; циклізація; X-ray structural analysis; Рентгеноструктурний аналіз